Effectiveness of a quality-improvement program in improving management of primary care practices - Szecsenyi, Joachim; Campbell, Stephen; Broge, Bjoern; Laux, Gunter; Willms, Sara; Wensing, Michel; Götz, Katja (The Canadian Medical Association journal, 2011)
Background: The European Practice Assessment program provides feedback and outreach visits to primary care practices to facilitate quality improvement in five domains (infrastructure, people, information, finance, and quality and safety). We examined the effectiveness of this program in improving management in primary care practices in Germany, with a focus on the domain of quality and safety. - Methods: In a before-after study, 102 primary care practices completed a practice assessment using the European Practice Assessment instrument at baseline and three years later (intervention group). A comparative group of 102 practices was included that completed their first assessment using this instrument at the time of the intervention group’s second assessment. Mean scores were based on the proportion of indicators for which a positive response was achieved by all of the practices, on a scale of 0 to 100. - Results: We found significant improvements in all domains between the first and second assessments in the intervention group. In the domain of quality and safety, improvements in scores (mean scores were based on the proportion of indicators for which a positive response was achieved by all of the practices, on a scale of 0 to 100) were observed in the following dimensions: complaint management (from a mean score of 51.2 at first assessment to 80.7 at second assessment); analysis of critical incidents (from 79.1 to 89.6); and quality development, quality policy (from 40.7 to 55.6). Overall scores at the time of the second assessment were significantly higher in the intervention group than in the comparative group. - Interpretation: Primary care practices that completed the European Practice Assessment instrument twice over a three-year period showed improvements in practice management. Our findings show the value of the quality-improvement cycle in the context of practice assessment and the use of established organizational standards for practice management with the Europeaen Practice Assessment.